Analisis Saluran dan Efisiensi Pemasaran Sayuran Hidroponik di KUTP Hidrotani Sejahtera Desa Suka Maju Kecamatan Sunggal Kabupaten Deli Serdang - Ahmad Sutan Nauli Lubis; Gustami Harahap; Mitra Musika Lubis (Universitas Medan Area, 2021)
The purposes of this study are to determine the hydroponic vegetable marketing channels and efficiency level of hydroponic vegetables’ marketing channels in KUTP Hidrotani Sejahtera Suka Maju Village, Sunggal District, Deli Serdang Regency. The research method used in this study was purposive sampling method. The sample of this research were 28 samples. Based on the survey conducted there were 2 modern markets as retailer, Brastagi Supermarket and Transmart Carrefour which sell hydroponic vegetables. Twenty-five customers were taken as samples. The method used was snowball sampling and Microsoft Excel calculation methods. Data used were primary and secondary data. The study was conducted in May 2019. The results showed that the marketing channel for hydroponic vegetable in KUTP Hidrotani Sejahtera began from producers to retailers then last to consumers. The hydroponic vegetable marketing channel at the level of the marketing agency was an efficient with efficient level of 0.15%.